Askgödsling och dess lämplighet i torvmarksskogar tillhörande Sveaskog Förvaltnings AB : en litteraturstudie - Norrbom, Tobias (SLU/Dept. of Forest Ecology and Management, 2008)
During whole-tree harvesting, there is a risk that the soil will become impoverished of nutrients. To prevent this, nutrients are returned to the harvested site as wood ash. This action also reduces the risk of soil acidification. Nevertheless, the ash does not result in any increase of tree growth if it is added on mineral soils, which is where the measure is most commonly used in Sweden. Due to the lack of growth response, the interest from landowners is small, which is why ash amendment today is not done enough to compensate for the need. On the other hand, if the ash is added on organic soils, several studies show that an obvious gain in tree growth can be achieved. This is because the ash contains all the nutrients that a tree needs, except for nitrogen. On organic soils, the lack of nitrogen is usually not a problem, in contrast to mineral soils.